(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2021)
Plant biotechnology is an área of high importance since it has the function of obtaining plant organisms with characteristics superior to those already on the market. Cloning is one of the tools that can be used for this function, through it, organisms with characteristics of interest are selected and this individual is multiplied, ensuring that the regenerated plants are genetically identical to the desired matrix, establishing a standardization. Knowing that the ornamental plants sector contributes significantly to the economy and among the most esteemed ornamental plants among Brazilians, there are orchids which have acquired cultural visibility and a large number of collectors in recent years. The objective of the present work was to establish an efficient assepsis protocol for lateral meristems and to obtain clones of the orchid of the genus Phalaenopsis. For methodology, aiming at the standardization o fan asepsis protocol, 4 treatments were developed and tested with different combinations (concentration x time) of agents such as sodium hypochlorite, alcohol, copper, tween and washing the explants with sterile distilled wáter for meristems of the orchid of the genus Phalaenopsis. The meristems, also known as lateral buds, were removed from the stem of the seedlings, from their floral stems. As for obtained clones, the experiment carried out consisted of inoculating the meristems, after an asepsis process, in Knudson culture media, containing different combinations of growth regulators, using an auxin and cytokinin. The results obtained show that, no asepsis treatments tested in this work, presented significant and positive results, so it was not posible to establish, as yet, an asepsis protocol for lateral meristem of orchids of the genus Phalaenopsis. Since all meristems suffered contamination and oxidation. Therefore, it was not yet posible to obtain clones, using this methodology. This work serves as an initial basis, for future research, regarding cloning through meristems in Phalaenopsis.